Differences in perceived predation risk associated with variation in relative size of extra‐pair and within‐pair offspring. (28th November 2019) - Hallinger, Kelly K.; Vitousek, Maren N.; Winkler, David W.
Abstract: Extra‐pair paternity (EPP) is a widespread phenomenon in birds. Researchers have long hypothesized that EPP must confer a fitness advantage to extra‐pair offspring (EPO), but empirical support for this hypothesis is definitively mixed. This could be because genetic benefits of EPP only exist in a subset of environmental contexts to which a population is exposed. From 2013 to 2015, we manipulated perceived predator density in a population of tree swallows ( Tachycineta bicolor ) breeding in New York to see whether fitness outcomes of extra‐pair and within‐pair offspring (WPO) varied with predation risk. In nests that had been exposed to predators, EPO were larger, longer‐winged and heavier than WPO. In nonpredator nests, WPO tended to be larger, longer‐winged and heavier than EPO, though the effect was nonsignificant. We found no differences in age, morphology or stress physiology between extra‐pair and within‐pair sires from the same nest, suggesting that additive genetic benefits cannot fully explain the differences in nestling size that we observed. The lack of an effect of predator exposure on survival or glucocorticoid stress physiology of EPO and WPO further suggests that observed size differences do not reflect more general variation in intrinsic genetic quality. Instead, we suggest that size differences may have arisen through differential investment into EPO and WPO by females, perhaps because EPO and WPO represent different reproductive strategies, with each type of nestling conferring a fitness advantage in specific ecological contexts. Abstract : Tree swallow (Tachycineta bicolor) nestlings reared under heightened predation risk differ in size based on their paternity status ‐ extra‐pair offspring are larger than within‐pair offspring when predation risk is experimentally elevated. Interestingly, within‐pair offspring tend to be larger than extra‐pair offspring when perceived predation risk is relatively lower, suggesting that extra‐pair and within‐pair offspring may not fall along the simple "high genetic quality" vs. "low genetic quality" spectrum to which they are often assigned. Photo of tree swallow by David W. Winkler.